Health Belief Model Application in Encouraging Colorectal Cancer Screening in Adults: Meta-analysis - Audria Ersananda; Aulia Siti Nur Rahmah (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Colorectal cancer is one of the cancers caused by the growth of malignant abnormal cells in the large intestine and rectum which are part of the gastrointestinal system. Screening has the potential to reduce the burden of colorectal cancer with the support of scientific literature showing a reduction in colorectal cancer mortality ranging from 18% to 57% (depending on the screening test used). The Health Belief Model is a health behavior model that can predict a person's interest in screening for colorectal cancer. This study aims to estimate the effect of the Health Belief Model in colorectal cancer screening by meta-analysis.Subjects and Method: Meta-analyses were performed by searching articles from the PubMed, Google Scholar, and ScienceDirect databases. The keywords and Boolean operators used are Health Belief Model OR perceived susceptibilty OR perceived risk OR risk perception OR perception of risk AND screening colorectal OR colonoscopy OR faecal occult blood test OR sigmoidoscopy. The inclusion criteria in this study were full-text articles with a cross-sectional design. The articles were published in English from 2012 to 2022. The population used in this study were both male and female adults. Analysis of perceived susceptibility to final study results was reported using the adjusted odds ratio (aOR). Article analysis using RevMan 5.3 software.Results: A total of 9 articles were used. The results showed that a person's perception of being vulnerable or at high risk will increase colorectal cancer screening by 1.81 times compared to someone who has a low perception of susceptibility to colorectal cancer screening (aOR= 1.81; 95% CI= 1.58 to 2.07) and the results are significant. statistically (p < 0.001).Conclusion: Perceived susceptibility is statistically significant in predicting someone to be screened for colorectal cancer.Keywords: health belief model, susceptibility perception, colorectal cancer screening.Correspondence:Aulia Siti Nur Rahmah. Catholic School of Health Sciences, St.Vincentius A Paulo, Surabaya, East Java, Indonesia. Email: rahmaaulia500@gmail.com. Mobile: +6281233511180Journal of Health Promotion and Behavior (2021), 06(04): 327-338DOI: https://doi.org/10.26911/thejhpb.2021.06.04.07